Analysis of Differentially Expressed Proteins in Mycobacterium avium-Infected Macrophages Comparing with Mycobacterium tuberculosis-Infected Macrophages. (10th May 2017) - Yang, Dongjun; Fu, Xin; He, Shiyi; Ning, Xueping; Ling, Min
Abstract : Mycobacterium avium (MA) belongs to the intracellular parasitic bacteria. To better understand how MA survives within macrophages and the different pathogenic mechanisms of MA and Mycobacterium tuberculosis (MTB), tandem mass tag (TMT) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis have been used to determine the proteins which are differentially expressed in MA-infected and MTB-infected macrophages. 369 proteins were found to be differentially expressed in MA-infected cells but not in MTB-infected cells. By using certain bioinformatics methods, we found the 369 proteins were involved in molecular function, biological process, and cellular component including binding, catalytic activity, metabolic process, cellular process, and cell part. In addition, some identified proteins were involved in multiple signaling pathways. These results suggest that MA probably survive within macrophages by affecting the expression of some crucial proteins.